An Overview of Regulation in Mobile Telecommunications Markets - Castro Monge, Edgar (2011)
Despite the fact that most industries are imperfectly competitive to some extent,governments have been sensitive to the inefficiencies arising from imperfectcompetition. Not all the times prices and profits of monopolies are regulated.Moreover, antitrust law prohibits certain practices such as collusive pricing, a characteristic of oligopolistic firms, and agreements to share markets. All theseinitiatives are aimed at promoting perfect competition and achieving economy efficiency. Their common objective is to limit the market power of monopolies and oligopolistic firms, and fight against the perceived failures in the market, where individuals can not have enough information or capacity to protect themselves. For this reason, the State relies on the regulation or deregulation of certain sectors and industries to encourage competition and prevent monopoly abuse by banning certain types of anticompetitive practices. Given this scenario, the regulation of mobile telephony is analyzed in this article since it can provide important information as a result of Costa Rica openness to the mobile market.